Exploration of combined physical activity and music for patients with Alzheimer’s disease: A systematic review - Li, Kailimi; Cui, CanCan; Zhang, Haipeng; Jia, Luning; Li, Rui; Hu, Hao-Yu (Frontiers in Aging Neuroscience, 2022)
Objective: Alzheimer’s disease (AD) can be treated in different ways, one of which is combined physical activity and music intervention, which is a complementary therapy to a non-pharmacological one. This study provided a thorough systematic review on the application of combined physical activity and music intervention in patients with AD Methods: This study was performed based on the preferred reporting items for randomized control trails, crosscover study, case report and single subject design study. Online sources, such as PubMed, Web of Science, SAGE Premier, EBSCO, and Cochrane, published from January to March 2022 were searched for articles in the field. Results: The systemic review looked at eight studies, two of which had high methodological quality and six were moderate. Various types of research were included: five RCTs, one single-subject study, one crossover study, and one case report. Music intervention was conducted during an exercise program (n=6). A cognitive stimulation was applied with music therapy and physical activities (n=2). The physical activities or movements included balance training, stretching, strengthening, and different sports activities. Outcome assessment, including the Barthel index (n=2) and the functional independence measure, was conducted to evaluate the daily functional score. Mental health was evaluated by Mini-Mental State Examination (n=3). Conclusion: Combined physical activity and music intervention are beneficial and improve the cognitive, physical, and well being of patients with AD. A higher quality of research that uses rigorous methods, including longer interventions and larger samples, should be conducted to determine the optimum parameters of music-based physical activities.